2021
DOI: 10.1055/s-0041-1739411
|View full text |Cite
|
Sign up to set email alerts
|

2021 Focused Update Consensus Guidelines of the Asia Pacific Heart Rhythm Society on Stroke Prevention in Atrial Fibrillation: Executive Summary

Abstract: The consensus of the Asia Pacific Heart Rhythm Society (APHRS) on stroke prevention in atrial fibrillation (AF) has been published in 2017 which provided useful clinical guidance for cardiologists, neurologists, geriatricians, and general practitioners in the Asia-Pacific region. In these years, many important new data regarding stroke prevention in AF were reported. The practice guidelines subcommittee members comprehensively reviewed updated information on stroke prevention in AF, and summarized them in this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
245
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 316 publications
(252 citation statements)
references
References 220 publications
(358 reference statements)
7
245
0
Order By: Relevance
“…may discourage the incorporation of GDF-15 in guidelines related to antithrombotic therapy, where simplicity and practicality for decision making should be prioritized. 32 33 34…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation
“…may discourage the incorporation of GDF-15 in guidelines related to antithrombotic therapy, where simplicity and practicality for decision making should be prioritized. 32 33 34…”
Section: Tablementioning
confidence: 99%
“…may discourage the incorporation of GDF-15 in guidelines related to antithrombotic therapy, where simplicity and practicality for decision making should be prioritized. [32][33][34] Moreover, a limitation of GDF-15 is the lack of real-world studies given that most of the evidence is derived from randomized clinical trials. This is relevant for the particular issue of bleeding since one recent study suggested that differences in patient characteristics and risk profiles of patients from observational studies are important contrib-utors to the differences in bleeding outcomes between clinical practice and randomized trials.…”
mentioning
confidence: 99%
“…This is proposed in the Atrial Fibrillation Better Care (ABC) pathway, where ‘A’ refers to ‘Avoid stroke’; ‘B’ refers to ‘Better symptom management’ and ‘C’ refers to ‘Cardiovascular and comorbidity risk reduction’ [ 7 ]. Recently, the 2020 European Society of Cardiology guidelines on the management of AF, as well as other international guidelines, have recognized this need for a more integrated care, by including for the first time the ABC pathway as a simplified and concise approach that integrates the care of AF patients across various levels of healthcare professionals and between specialties [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The importance and evident benefits of a well‐rounded holistic and integrated approach to evaluation, characterization, and management of atrial fibrillation (AF) have been emphasized in recent guidelines. 1 , 2 , 3 Standardizing holistic management through protocolization and implementation of framework models can lead to improved patient care. 4 , 5 The Atrial Fibrillation Better Care (ABC) pathway promotes such an integrated approach to AF management 6 : (A) avoid stroke; (B) better symptom control, with patient‐centered symptom‐guided decisions on rate or rhythm control; and (C) cardiovascular risk factor and comorbidity optimization, including lifestyle changes.…”
mentioning
confidence: 99%